If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 + -6n = 4(7n + 8) Reorder the terms: -26 + -6n = 4(8 + 7n) -26 + -6n = (8 * 4 + 7n * 4) -26 + -6n = (32 + 28n) Solving -26 + -6n = 32 + 28n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-28n' to each side of the equation. -26 + -6n + -28n = 32 + 28n + -28n Combine like terms: -6n + -28n = -34n -26 + -34n = 32 + 28n + -28n Combine like terms: 28n + -28n = 0 -26 + -34n = 32 + 0 -26 + -34n = 32 Add '26' to each side of the equation. -26 + 26 + -34n = 32 + 26 Combine like terms: -26 + 26 = 0 0 + -34n = 32 + 26 -34n = 32 + 26 Combine like terms: 32 + 26 = 58 -34n = 58 Divide each side by '-34'. n = -1.705882353 Simplifying n = -1.705882353
| (2x^2)+(8x)+(2y^2)=0 | | 3.9v+2.4=0.9v+5.4 | | 8-6t=-16 | | 96=L*w-4 | | 3k+(2k+5)= | | t-ma=w | | ((3t-8)/(10t-3))=0 | | (2x^2)+(8x^2)+(2y^2)=0 | | 3(5x-5)=8x+13 | | 175=6x+8x | | 4.32+4m=6.48 | | -3x+4x=8-x | | 0=6v-9 | | 6.3x-4=2.6x-3 | | -23+4m=57 | | 23(j+2)=4j | | 9.4=d+5.6 | | 8j-5=11 | | 2(4x-1)=3(x+3)-2 | | 6zy-2z= | | (y+5)+1=3y | | 2x^0= | | 23v-40=23 | | -4j+8=-32 | | (3x)-20=43 | | 1/3x-y=7 | | y=2.6x-4.2 | | n-4-5=-12 | | -4j+8=32 | | 23=x/3 | | 8+13n-1=9n+27-6n | | 8v-17=-17 |